Cyborg. Nomadic thinking and aesthetic drift - Vega Baeza, Rita (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Since the sequencing of the human genome was completed, man loses his “essence”, becoming an interpretable and modifiable text: a subversion of the flesh. D. Haraway (1995) has been one of the pioneers on the subject, defending the cyborg as a controversial entity, a cyberorganism that questions, from a certain perspective of the philosophy of technique, –and even feminisms– in which they are inscribed, also Sloterdijk, Sandel, T. Aguilar, among others, the alleged humanist essence, which is questioned around “the human” and its univocal identity. Aesthetic drifts of Orlan, Sterlac and Kac are analyzed.